1999
DOI: 10.1007/s000180050312
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinases: which one is the memory molecule?

Abstract: Encoding of new experiences is likely to induce activity-dependent modifications in the brain. Studies in organisms far apart on the phylogenetic scale have shown that similar, sometimes identical, signal transduction pathways subserve plasticity in neuronal systems, and they may play pivotal roles in the formation of long-term memories. It has become evident that phosphorylation/dephosphorylation reactions are critical for the initiation of cellular mechanisms that embody, retain and modify information in neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(70 citation statements)
references
References 118 publications
1
68
1
Order By: Relevance
“…While many studies have suggested the importance of cAMP signaling in associative learning (Micheau and Riedel 1999;Fiel et al 2005;Margulies et al 2005;McGuire et al 2005;Hofmann et al 2006), our results implicate the cGMP signaling pathway in mediating reward learning and memory. Specifically, our results suggest a novel role for the foraging gene in larval learning and memory.…”
Section: Discussioncontrasting
confidence: 49%
“…While many studies have suggested the importance of cAMP signaling in associative learning (Micheau and Riedel 1999;Fiel et al 2005;Margulies et al 2005;McGuire et al 2005;Hofmann et al 2006), our results implicate the cGMP signaling pathway in mediating reward learning and memory. Specifically, our results suggest a novel role for the foraging gene in larval learning and memory.…”
Section: Discussioncontrasting
confidence: 49%
“…The Ca 2+ /CaM-dependent protein kinase II (CaMKII) has been linked to neuronal plasticity associated with long-term potentiation as well as with structural synaptic plasticity (Micheau and Riedel 1999). Previous work in adult honeybees has shown that the single CaMKII gene found in honeybees is strongly expressed in the mushroom bodies (MBs) (Kamikouchi et al 2000), brain centers associated with sensory integration, learning, and memory formation (Giurfa 2007;Giurfa and Sandoz 2012).…”
Section: Experiments 5: Inhibition Of Camkii Impairs L-ltm Retentionmentioning
confidence: 99%
“…That would be a nice starting point: to look for those substrates. The bad news is that now it's known that PKA and the extracellular signal-regulated kinase system are truly enmeshed, cross-talk a lot with each other, and cross-talk with protein kinase C (PKC) a lot (27).…”
Section: Larry Cahillmentioning
confidence: 99%